Building the New Socialist Person: Key Issues in Grecophone School Reading Textbooks of the Soviet Union, 1927–1937 - Papastefanaki, Eleftheria; Papathanasiou, Christos; Vafeas, Nikos; Athanasiades, Harris (Historein, 2023)
This study explores the concept of the new socialist person as it emerges from the pages of interwar Soviet readers for Grecophone populations. It focuses on the modifications the concept underwent to meet conjunctural needs and in the context of the social, political, ideological and economic changes in the USSR and the politics of the communist parties. The building of the new socialist person involved a renegotiation of identity markers such as gender and nationality, which were subordinated to a labour-centred picture. Accordingly, the new citizen identity was defined in terms of participation in the fulfilment of production targets, socialist emulation, defence of the socialist homeland and political participation in Communist Party organisations as mediated by the personality cult and total respect for hierarchy.